2002
DOI: 10.1254/jjp.88.217
|View full text |Cite
|
Sign up to set email alerts
|

Abatement of Morphine-Induced Slowing in Gastrointestinal Transit by Dai-kenchu-to, a Traditional Japanese Herbal Medicine

Abstract: ABSTRACT-As a way of alleviating severe constipation in cancer patients taking morphine to relieve pain, effects of Dai-kenchu-to (DKT), a traditional Japanese herbal medicine (Kampo medicine), on gastrointestinal transit in mice or on the isolated guinea pig ileum were studied in special reference to morphine. Without altering the anti-nociceptive effect of morphine, DKT was significantly effective against morphineinduced disorder of gastrointestinal transit in mice as assessed by the charcoal meal test for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 14 publications
1
27
0
1
Order By: Relevance
“…The mechanism of DKT is gradually elucidated; several studies show that DKT accelerates the gastrointestinal transit [9][10][11][12][13][14][15]. As delayed intestinal transit could be responsible for increased endoluminal bacterial overgrowth, DKT may have a positive effect in preventing this occurring.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of DKT is gradually elucidated; several studies show that DKT accelerates the gastrointestinal transit [9][10][11][12][13][14][15]. As delayed intestinal transit could be responsible for increased endoluminal bacterial overgrowth, DKT may have a positive effect in preventing this occurring.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a Chinese herbal medicine, known as Rikkunshi-to and TJ-43, has been reported to enhance gastric emptying (30) and gastric adaptive relaxation (31). It has been demonstrated that daikenchuto, a Japanese herbal medicine comprised of four herbs, is able to ameliorate morphine-induced inhibition of intestinal and colonic transit (32). However, the optimal therapeutic strategy for FGID remains to be determined due to the poorly defined pathogenesis of the condition.…”
Section: Discussionmentioning
confidence: 99%
“…23 Daikenchuto is thought to have a restorative effect on delayed gastrointestinal transit in duced by intestinal manipulation and morphine administration. 22,24 Although a total gastrectomy is widely performed for the treatment of gastric carcinoma, there is no general agreement about ideal reconstruction. To provide reservoir function and to improve nutritional conditions, many types of jejunal pouch reconstruction have been described and evaluated.…”
Section: Effect Of Dkt On Postoperative Ileusmentioning
confidence: 99%